Restriction polymorphism maps of Neurospora crassa: update - R. L. Metzenberg; J. Grotelueschen (Fungal Genetics Reports, 1989)
When a gene or other fragment of DNA is cloned. it is often useful to identify the chromosomal region from which it arose.